Mortgage-backed securities : products, structuring, and analytical techniques - 388022 Fabozzi, Frank J.; Bhattacharya, Anand K. 235496; Berliner, William S. 235501 (Hoboken, N.J. : Wiley)
Includes bibliographical references and index